‫أثر‬‫الرفع‬ ‫المالي‬ ‫على القرار ‬ ‫الاستثماري ‬ ‫‫في‬ ‫مطاحن‬ ‫بلغيث‬ ‫الكبرى‬ ‫ ‬‫مداوروش‬ 2011-2015‫‪‬‬‫للفترة‬ ‫‬ ‬ - ‬حياة بوروبة ‬; ياسمينة ماجرالو (My University, 2017)
The existence of the institution is linked to the extent to which its investments are successful in achieving sufficient financial revenues that are afforded by sustainability, competition and survival The decision-making process on investment projects is one of the most difficult decisions facing the financial path in the institution, because of the huge amounts of money it requires and its dependence on future forecasts, which makes it a high risk. This requires the institution to balance the costs and revenues achieved through the investment through accreditation. On more rational criteria in the feasibility study of their investment projects In order to become familiar with this issue, which is considered important in light of the increase in competitiveness, this will be dropped on the major mills of Belghith, which recently benefited from financing loans with multiple funding sources in order to determine the result of the financial leverage on its financial decisions